Introduction - Anheier, Helmut K. (Innovation in strategic philanthropy, 2007)
During much of the 1990s, philanthropy thrived both nationally and internationally. By the turn of the century, there were more foundations holding more assets in more countries than ever before. Although endowment values dropped since then, they remain at historically high levels in most developed market economies. What is more, new forms of philanthropy have emerged in the course of the last decade, with donor circles, donor advised funds, and e-philanthropy adding new momentum to the growing phenomenon of transnational, philanthropic action.